2016
DOI: 10.1371/journal.pone.0166388
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Igf1r in Bronchiolar Epithelial Regeneration: Role during Repair Kinetics after Selective Club Cell Ablation

Abstract: Regeneration of lung epithelium is vital for maintaining airway function and integrity. An imbalance between epithelial damage and repair is at the basis of numerous chronic lung diseases such as asthma, COPD, pulmonary fibrosis and lung cancer. IGF (Insulin-like Growth Factors) signaling has been associated with most of these respiratory pathologies, although their mechanisms of action in this tissue remain poorly understood. Expression profiles analyses of IGF system genes performed in mouse lung support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 100 publications
1
21
1
Order By: Relevance
“…Additionally, decreased eosinophilopoiesis in bone marrow of Igf1r deficient mice can also substantially contribute to reduced eosinophil presence in the lung. The proposed mechanism illustrated in this figure is supported by results from the present study and additional reports [ 12 , 20 , 28 , 29 , 36 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, decreased eosinophilopoiesis in bone marrow of Igf1r deficient mice can also substantially contribute to reduced eosinophil presence in the lung. The proposed mechanism illustrated in this figure is supported by results from the present study and additional reports [ 12 , 20 , 28 , 29 , 36 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additional reports have shown that IL33 exacerbates murine allergic bronchoconstriction and that resolution of allergic airway inflammation and AHR is dependent upon disruption of IL33 signaling in mice [ 27 , 28 ]. Notably, lung epithelial-specific Igf1r deficiency in mice caused delayed differentiation of the airway epithelium, a major source of IL33 [ 29 , 30 ]. IGF1R - deficient lungs showed a reduced proportion of club cells in distal airways after chronic HDM exposure [ 12 ] and therefore this phenomenon could be manifested as a reduced IL33 release from the airway epithelium by HDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of Igf1, Insr, Igfbp3, and Igfbp5 in PBS-exposed mice is possibly a compensatory effect in response to Igf1r deficiency, as we have previously reported in lungs from mice with compromised Igf1r signaling in the respiratory epithelium. 13 Accordingly, it has been previously reported that exogenous Igfbp3 and Igfbp5 administration blocks physiological consequences of asthma in OVA-challenged mice and enhances epithelial cell adhesion to maintain the epithelial-mesenchymal boundary. 8,9,16 Thus, Igfbp3 and Igfbp5 could mediate protective properties against HDM-mediated allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced proportion of club cells found in distal airways of CreERT2 mutant lungs is in accordance with recent data published by our group where a lung epithelial-specific Igf1r deficiency in mice caused delayed differentiation of club cells in terminal bronchioles. 13 In response to allergen stimulation, club cells differentiate into goblet cells through transcriptional activation of the master regulator Spdef.…”
Section: Discussionmentioning
confidence: 99%